Et opgør om synden hos Plesnerfamilien: med baggrund i de fynske præstebrødres nyortodoksi - Rasmussen, Jens (Kirkehistoriske Samlinger, 2017)
Johan Fr. Plesner (1815-1892) var som ung teologisk kandidat blevet vakt ved de gudelige forsamlinger i Humble sogn på Langeland. Hans første krise kom i begyndelsen af 1850’erne, da han som kapellan skulle prædike i Bøstrup kirke. Johan Fr. Plesner læste Luthers skrifter og spurgte sig selv, hvordan han kunne bruges til forkynder. Det kom til et opgør med faderen, provst Ulrich Adolph Plesner (1782-1861), Humble sogn. Sønnens syn på syndens totalt fordærvende menneskenatur blev ikke delt af faderen. I 1856 blev Johan Fr. Plesner sognepræst i Vedersø, og her fortsatte hans sjælekvaler. Han tilhørte den fynske kreds af grundtvigske præstebrødre, og han fik stor hjælp under sine kriser fra C. Fr. Kisbye i Aunslev og Vilh. Birkedal i Ryslinge. Sidstnævnte havde også oplevet en krise i 1847-48. Hans prædikensamling fra 1848 var præget af nyortodoksiens forkyndelse af synd og nåde ud fra læren om lov og evangelium. Denne forståelse kom også til udtryk i Johan Fr. Plesners Luther-udgivelser og i hans breve til faderen (U.A. Plesners privatarkiv). Brevene er ikke tidligere beskrevet detaljeret. Summary Coming to terms with sin in the Plesner family – in the context of neo-orthodoxy. In the 1840’s the young theologian candidate Johan Frederik Plesner (1815-1892) felt a spiritual revelation when he attended revivalist movement assemblies in the parish of Humble on the island of Langeland, where his father was rural dean. Study of Martin Luther’s writings made J.F. Plesner uneasy about his ability to preach the gospel to the congregation. During the years 1850-52, when Plesner was a curate in the parish of Bøstrup, he was suffering a crisis. Consequently Plesner was hospitalised in Frederik’s Hospital in Copenhagen. In 1856 J.F. Plesner became vicar of the parish of Vedersø, here his mental sufferings continued. It came to a clash with his father Ulrich Adolph Plesner (1782-1861), rural dean of Humble. Beginning in 1855, the problems continued till the father’s death. The strained relationship came out in the son’s letters to his father. The letters have not been examined in detail until now with the present study (U.A. Plesner’s private archive). In a debate on original sin the son’s view that sin completely corrupts human nature is not shared by his father. J.F. Plesner belonged to the circle of Grundtvigian preachers in Funen. In times of crisis Plesner received much help and support from the pastors C.F. Kisbye, Aunslev and V. Birkedal, Ryslinge. The latter had also been suffering from a mental crisis in 1847-48. His collection of sermons from 1848 to 1849 was dominated by orthodoxy, preaching of sin and grace according to the teaching of law and evangelism. Such understanding was also expressed in J.F. Plesner’s edition of Luther’s writings as well as in his letters to his father. For several years, both J.F. Plesner and V. Birkedal had to fight the burden af sin, the ambiguous heritage from Reformation theology.